Meta-analytical evaluation of the clinical efficacy of a complex metabolic neuroprotector in patients with chronic cerebral ischemia - M. V. Zhuravleva; G. I. Gorodetskay; T. S. Reznikova; N. S. Vasyukova; V. V. Arkhipov; S. Yu. Serebrova (Антибиотики и Химиотерапия, 2022)
The aim of the study is to evaluate the clinical efficacy, safety, and impact of the complex metabolic neuroprotector on the patients’ quality of life (CMN) Cytoflavin in tablets, as well as in the course of stepwise pharmacotherapy of patients with chronic cerebral ischemia (CCI) of various etiologies, followed by meta-analysis, on the basis of a systematic review of published clinical studies.Material and methods. A selection of randomized controlled trials was carried out over the past 15 years, in which CMN Cytoflavin was used in the tablet dosage form or in a stepwise course of therapy in at least 25 patients diagnosed with chronic cerebral ischemia with a total course of therapy of at least 25 days. The assessment of CMP clinical efficacy and the analysis of formalized indicators of clinical efficacy (relative risk, odds ratio, frequency of outcomes, values of absolute and relative benefits, etc.) was carried out.Results and conclusion. 403 publications for 2000–2017 describing the use of CMN Cytoflavin were analyzed. 16 studies were selected for the systematic review, the meta-analysis included 6 randomized clinical trials and one non-randomized study of the use of CMN in patients with CCI. The data of the systematic review and meta-analysis showed a sufficient efficacy of complex metabolic neuroprotector use in patients with chronic cerebral ischemia. However, the meta-analysis revealed significant heterogeneity between the studies. The drug has a beneficial effect on the quality of life of patients, increases the likelihood of a positive outcome in relation to the relief of asthenic and vestibular-atactic syndromes, in relation to complaints of increased fatigue, headache, dizziness, noise in the head, impaired coordination. It improves cognitive functions, exhibits sufficiently high tolerance and safety.